‘Hopeful’ directions for writing centres in South Africa: From safe spaces to transitional sites of articulating practice - Nichols, Pamela (Stellenbosch Papers in Linguistics Plus, 2017)
I shall orientate the discussion of the directions of writing centres in South Africa around two beginnings. The first is the 1995 conference at the University of the Western Cape at which representatives from universities across the country discussed the new (in South Africa) idea of the writing centre and its local, varied applicability, and the second is the continuing student protests since 2015, which demand a re-theorising of the role of writing centres. This re-theorising requires a revisiting of explicitly anti-exclusionary practice and the theory of what we do when we listen. Using the work of Lisa Delpit (1995) and her reflections on how the American system of education has failed the majority of African Americans and other ‘outside’ groups, I shall investigate her understanding of listening and connectedness for greater pedagogic inclusiveness. Then through considering the work of Nancy Grimm (1999), I shall discuss the theory of the transitional space, which resonates with Delpit’s conclusions and which explicitly seeks not to normalise or erase difference but rather to find its articulation. Lastly, I shall evoke James Baldwin as a master articulator of difference, as a writer who expresses a fluidity of subjectivity and as a cultural alternative to explicitly ideological and political responses to a time of crisis. The current resurgence of Baldwin studies and the success of the recent documentary based entirely on Baldwin’s words (Peck 2017) suggest the appeal of Baldwin’s voice now as someone who moves us beyond labels and makes us see each other and see ourselves as others see us.